Perancangan Elemen Interior Musikal - Filipus Priyo Suprobo, Sherly Widyawati Yusita Kusumarini (Intra, 2014)
Musical Interior Element is an interior element which functionÂ is combined with the function of musical instruments. The Interior elements consist of flooring, wall, ceiling and other object, such as furniture. Musical interior elements aims to propose a non-visual aspects of the interior elements of sound that is produced by the material. The target of this musical is for all ages which make the design easy to play, therefore musical interior designed with a simple form that is easy to play. To convey what it is not enough musical interior elements designed on paper only because the author uses a 1:1 prototype. The design method used is the method of experiment and research on related objects, namely the interior elements and musical instruments to get the opportunities or possibilities of any interior elements that can be combined with the function of musical instruments.